Consolidation With Pembrolizumab and Nab-Paclitaxel After Induction Platinum-Based Chemotherapy for Advanced Non-Small Cell Lung Cancer - Patel, Shetal A.; Gerber, David E.; Deal, Allison; Douglas, Kathe; Pecot, Chad V.; Lee, Carrie; Schiller, Joan; Dhruva, Nirav; Weiss, Jared (Frontiers in Oncology, 2021)
Background: Induction with four cycles of platinum-based chemotherapy was the standard of care for metastatic non-small cell lung cancer (NSCLC) until the approval of immune checkpoint blockade (ICB) in the first line setting. Switch maintenance therapy has shown promise in improving survival by exposing patients to novel, non-cross resistant agents earlier in their treatment course. Methods: We performed this open-label, three-arm, randomized phase II study (NCT02684461) to evaluate three sequences of consolidation with pembrolizumab and nab-paclitaxel in patients without progressive disease post induction chemotherapy. Consolidation was either sequential with pembrolizumab for 4 cycles followed by nab-paclitaxel for 4 cycles (P->A), nab-paclitaxel followed by pembrolizumab (A->P), or concurrent nab-paclitaxel and pembrolizumab for 4 cycles (AP). Results: Twenty patients were randomized before the study was closed early due to the approval of first line checkpoint inhibitors. We found that consolidation is feasible and well-tolerated, with 30% of patients experiencing grade 3 toxicity. The median progression free survival and OS in months (95% CI) in P->A were 10.1 (1.5-NR), 27.6 (1.7-NR); 8.4 (1.2-9.0), 12.7 (4.4-NR) in A->P; and 10.2 (5.1-NR), NR. Quality of life as measured by FACT-L improved in the majority of patients during the course of the study. Conclusion: Sequential and concurrent consolidation regimens are well tolerated and have encouraging overall survival in patients with metastatic NSCLC.